Georg Forster in Vilnius: Reverberations of the great age of ocean navigation - Švambarytė, Dalia (Acta Orientalia Vilnensia, 2009)
Vilnius University This article discusses the contribution to the studies of the ‘Eastern’ and ‘Southern’ lands in the 18th century by naturalist, travel writer, and ethnologist George Forster, who had accompanied his father, Johann Reinhold Forster, on Captain James Cook’s expedition of 1772–5 to circumnavigate the globe and who was a professor of natural history at Vilnius University from 1784 to 1787. The paper presents the background of European long-distance navigation, examines Forster’s contribution to Cook’s second voyage, and reconsiders his work completed at the Vilnian Academy against the broader perspective of the European notions of travel literature and ethnography of the Pacific region, as well as the prospect of Oriental studies, gradually emerging as an academic field in Western Europe and, later on, in Vilnius.